2021
DOI: 10.1002/admt.202000857
|View full text |Cite
|
Sign up to set email alerts
|

Low Band Gap Conjugated Semiconducting Polymers

Abstract: Important parameters of an organic semiconductor material are the electronic band gap (Eg) and the position of highest occupied and lowest unoccupied bands versus vacuum. These bands are called valence and conduction band for inorganic semiconductors. For organic semiconductors the bands defining the band gap are often called highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO). One advantage of semiconducting polymers is the ability to tune the band gap and the position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
135
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(137 citation statements)
references
References 61 publications
2
135
0
Order By: Relevance
“…Various molecular engineering strategies have been applied to tune the bandgap of OSCs. Donor-acceptor (DA) CPs comprised of alternating electron-rich (donor) and electron-poor (acceptor) building blocks are now the dominant class of high-performance materials [6,181,182]. The combination of alternating donor (push) acceptor (pull) building blocks results in hybridization of molecular orbitals, HOMO and LUMO energy levels, and strong intramolecular charge transfer transitions that arise from contributions from the respective donor and acceptor units (Fig.…”
Section: Organicsmentioning
confidence: 99%
“…Various molecular engineering strategies have been applied to tune the bandgap of OSCs. Donor-acceptor (DA) CPs comprised of alternating electron-rich (donor) and electron-poor (acceptor) building blocks are now the dominant class of high-performance materials [6,181,182]. The combination of alternating donor (push) acceptor (pull) building blocks results in hybridization of molecular orbitals, HOMO and LUMO energy levels, and strong intramolecular charge transfer transitions that arise from contributions from the respective donor and acceptor units (Fig.…”
Section: Organicsmentioning
confidence: 99%
“…Recently,i th as become apparent that one of the most important obstacles that must be overcome in conjugated polymer design is the suppression of non-radiative decay in narrow band gap conjugated polymers. [10] Numerous recent studies have revealed that the high non-radiative voltage loss encountered in organic photovoltaics (OPVs), which holds back their efficiency, is primarily ac onsequence of the low solid state photoluminescence quantum yields (PLQYs) of the blend materials. [11,12] Hence,i ncreasing the PLQY of narrow band gap conjugated polymers is essential for next generation OPV,aswell as being appealing for light emitting diodes and biological imaging.I ti sc ommonly assumed that the close packing of conjugated polymers results in the creation of additional non-radiative decay pathways.T herefore,t he most promising strategy to increase the solid-state PLQY of conjugated polymers is to molecularly isolate the chains either through covalent or non-covalent encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike inorganic semiconductors, OSCs are not atomic solids, instead they form conjugated bonds constituted by a system of π delocalized orbitals. Therefore, important parameters of these systems are the band gap (E g ) and the position of the frontier molecular orbitals HOMO and LUMO [7]. An advantage of OSCs is the ability to precisely tune those parameters by molecular design, and small modifications of the chemical structure can lead to large changes in the electrical and optoelectronic behavior [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, important parameters of these systems are the band gap (E g ) and the position of the frontier molecular orbitals HOMO and LUMO [7]. An advantage of OSCs is the ability to precisely tune those parameters by molecular design, and small modifications of the chemical structure can lead to large changes in the electrical and optoelectronic behavior [7]. In the OSCs these values depend on structural factors such as their π-conjugated system, planarity, the presence of electroacceptor or electrodonor groups and the aromaticity of the rings.…”
Section: Introductionmentioning
confidence: 99%